Tuberculosis Knowledge in the Community: Insights and Gaps from Belkotgadhi, Nuwakot District, Nepal (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2025)
Background: Tuberculosis (TB) is a communicable disease and a major global public health challenge.The lack of knowledge about its communicable characteristics and treatment options is the main barrier to reducing its burden. This study aims to assess TB knowledge among people in Belkotgadhi Municipality, Nuwakot District.Methods: Data were collected from 3352 households across 12 wards of Belkotgadhi Municipality using a convenient sampling method. The data collected and stored in the Kobo Toolbox, included information on TB and sociodemographic variables. After excluding incomplete entries, 3331 households were analysed. Frequencies and percentages were calculated, and chi-square test was conducted to examine the association between TB knowledge and sociodemographic factors.Results: About 48.6% of respondents were unaware that TB is communicable, and 31.4% did not know it is treatable. The main prevention method identified was wearing masks in crowded areas (30%), followed by the BCG vaccine (22.7%); however, fewer than 10.0% were familiar with DOTS. The major source of health-related information was Health Workers. Knowledge of TB’s communicability was significantly associated with gender, age, religion, literacy, family type, and health insurance status. Lower knowledge was found among illiterate, older adults, females, Hindus, those living in joint families, and those without health insurance.Conclusion: Knowledge of TB is low, highlighting the need to increase awareness about its communicability, treatment,and prevention. It can be enhanced through educational interventions for various sociodemographic groups, as well as by sharing information via health service providers, television, radio, and social media.